Kesadaran Beragama Pada Masyarakat Islam Minoritas di Desa Gurusinga Kecamatan Berastagi Kabupaten Karo - Barasa, Nurainun Br; M, Maraimbang; Siregar, Husna Sari (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to study the form and dynamics of religious consciousness of Muslim community as a minority group in Gurusinga Village, Berastagi District, Karo County. The approach used was qualitative descriptive with data collection techniques through in-depth interviews, observation, and documentation. The results of the study indicate that despite being in a non-Muslim majority environment, Muslims in this village nevertheless demonstrate high religiosity, characterized by consistently performing worship services, involvement in religious collective activities, and a tolerant attitude towards embracing other religions. The main supporting factors that strengthen their religiosity include the role of religious figures, support from the village government, social harmony among religious communities, as well as a collective spirit as a minority community. On the other hand, challenges such as the proximity of worship facilities, the lack of religious teaching staff, the negative influence of social media, as well as economic pressures also continue to affect. This study provides an overview that religious consciousness can grow strongly in minority communities if it is supported by inclusive social structures and high internal solidarity.